DYNAMIC ANALYSIS OF UNIFORM AND NON-UNIFORM CROSS-SECTION CANTILEVER SANDWICH BEAMS - Hüseyinoğlu, Mesut; Şen, Murat; Yiğid, Osman; Çakar, Orhan (My University, 2019)
In this study, an analytical solution for dynamic analysis of uniform and nonuniformcross-section cantilever sandwich beam is presented. The sandwichbeam was assumed to be an Euler-Bernoulli beam and formed with a thin coreand two thin skin layers. So the shear deformations and rotational effects wereneglected. The equivalent flexural rigidity was obtained for the entiresandwich structure. Some implementations for the solution method are givenand the results are compared with numerical solutions. The usability of theEuler-Bernoulli Beam Theory for thin layered uniform or non-uniformsandwich beams is investigated. The solutions obtained from analytical andnumerical solutions are in good agreement.
Keywords: Mühendislik; Makine